2012
DOI: 10.1088/0026-1394/49/2/s34
|View full text |Cite
|
Sign up to set email alerts
|

Fourth World Radiometric Reference to SI radiometric scale comparison and implications for on-orbit measurements of the total solar irradiance

Abstract: We report the fourth World Radiometric Reference (WRR)-to-SI comparison. At the National Physical Laboratory we compared three transfer pyrheliometer instruments in power mode with the SI radiometric scale. Compared with the three previous comparisons, we improved the experiment by operating the transfer instruments in vacuum. At the Total solar irradiance Radiometer Facility (TRF) located at the Laboratory for Atmospheric and Space Physics (LASP) in Boulder, we repeated the power comparison of one of the tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 12 publications
0
44
1
Order By: Relevance
“…For example, the primary radiometer of SORCE/TIM experienced~200 ppm degradation over the first 10 years of operation (2003-2012Kopp 2014). PMO6 radiometers, which comprise both PREMOS radiometers and one half of the SOHO/VIRGO experiment (see below), can exceed thousands of ppm per decade (Fröhlich 2003;Schmutz et al 2013).…”
Section: Instrument Degradationmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the primary radiometer of SORCE/TIM experienced~200 ppm degradation over the first 10 years of operation (2003-2012Kopp 2014). PMO6 radiometers, which comprise both PREMOS radiometers and one half of the SOHO/VIRGO experiment (see below), can exceed thousands of ppm per decade (Fröhlich 2003;Schmutz et al 2013).…”
Section: Instrument Degradationmentioning
confidence: 99%
“…PMO6 radiometers, which comprise both PREMOS radiometers and one half of the SOHO/VIRGO experiment (see below), can exceed thousands of ppm per decade (Fröhlich 2003;Schmutz et al 2013). For example, the A-sensor of the PREMOS TSI radiometer on the PICARD satellite, ''PREMOS-A'', degraded by almost 3,000 ppm in 2 years of operation, during which it was exposed for 300 days (Fehlmann et al 2012;Schmutz et al 2013). This is why all TSI radiometers in space, other than the Hickey-Frieden (HF; Hickey et al 1988) and Earth Radiation Budget Satellite (ERBE; Lee et al 1995) experiments, had a backup channel in order to account for the degradation in the operating instrument (SORCE/TIM has three; Kopp & Lawrence 2005).…”
Section: Instrument Degradationmentioning
confidence: 99%
“…Longwave radiation is broadly defined as covering the ∼ 4-100 µm range (Petty, 2006), while the WISG pyrgeometers cover the range ∼ 4-50 µm (Eppley Precision Infrared Radiometer (PIR) pyrgeometers) and ∼ 4.5-42 µm (Kipp & Zonen CG(R)4 pyrgeometers). Recent measurements with newly developed high-precision ground-based radiometers have demonstrated that a revision of approximately −0.3 % and up to +5 W m −2 of the WSG and WISG scales, respectively, may be required (Fehlmann et al, 2012;Gröbner et al, 2014). Since a large number of shortwave and longwave radiation time series (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of radiometers are traceable to the World Standard Group (WSG) for shortwave radiation and the interim World Infrared Standard Group (WISG) for longwave radiation, hosted by the PhysikalischMeteorologisches Observatorium Davos/World Radiation Centre (PMOD/WRC, Davos, Switzerland). The WSG and WISG have recently been found to over-and underestimate radiation values, respectively (Fehlmann et al, 2012; Gröb-ner et al, 2014), although research is still ongoing. In view of a possible revision of the reference scales of both standard groups, this study discusses the methods involved and the implications on existing archives of radiation time series, such as the Baseline Surface Radiation Network (BSRN).…”
mentioning
confidence: 99%
“…variability that is of interest rather than the absolute radiative flux, we normalized the reconstruction and the VIRGO record to the TIM record, the absolute radiometry of which is widely accepted as the most accurate [40][41][42].…”
Section: The Tsi Model Is a Major Extension Of The Semi-empirical Modmentioning
confidence: 99%